Tinjauan Perlindungan Hukum terhadap Inovasi Teknologi Digital dalam Kerangka Hak Paten di Indonesia yang Berkepastian Hukum - Mierza Darsya Putra; Puguh Aji Hari Setiawan; Gradios Nyoman Tio Rae (CV Rewang Rencang, 2025)
The development of digital technology innovation in the era of globalization has posed new challenges in the intellectual property rights (IPR) protection system in Indonesia, especially in the field of patent rights. The legal problems that arise are related to the gap between das sollen and das sein, namely between the legal norms that govern patent protection and practices in the field that often face implementation obstacles. The absence of regulations that detail the unique characteristics of digital innovations, such as software-based inventions or algorithms, creates a legal vacuum. This has an impact on the weak legal certainty for inventors who need patent protection as a guarantee of ownership as well as an instrument for commercialization of their intellectual works. This study uses normative juridical research methods with a statutory approach and a conceptual approach. Research data was obtained through a literature review of related laws, court decisions, and academic sources from legal books and journals. The analysis was carried out by examining the synchronization between Law Number 13 of 2016 concerning Patents, Government Regulation Number 46 of 2020, and international legal instruments such as the TRIPS Agreement. The results of the study show that legal protection of digital technology innovations in the framework of patent rights in Indonesia still faces obstacles, both in terms of legal, institutional, and law enforcement substance. Existing regulations have not fully accommodated the need for digital innovation protection which is rapidly changing and borderless. The conclusion of this study emphasizes the need to update patent regulations to be more responsive to digital technology developments, as well as strengthening law enforcement mechanisms to ensure certainty and justice for inventors.